Building an Ethical Framework for European Pharmacists in e-Pharmacies - Alexandra Toma; Ofelia Crişan (Journal of Medical Internet Research)
Patients using e-pharmacies benefit substantially from their privacy and accessibility; however, they must also be aware of the health and safety risks. These risks can be mitigated through the implementation of robust legal and ethical frameworks. European pharmacists working in e-pharmacies are obligated to respect the legal frameworks governing the remote sale of medicines, as well as the rules of professional ethics, while considering the unique benefits and challenges of establishing online therapeutic relationships with patients. This Viewpoint paper aims to propose a comprehensive ethical framework for European pharmacists in e-pharmacies that promotes consistency and ensures patient rights while fostering professional integrity and responsibility. To this end, the codes of ethics of pharmacists in the European Union (EU) member states were explored to determine the extent to which they address e-pharmacies and to begin from their provisions the building of a shared ethical framework, supported by previously published findings. The ethical guidance provided by professional associations and other competent authorities of European pharmacists varies significantly across member states. In most EU member states, pharmacists’ codes of ethics do not contain rules addressing e-pharmacies. Only 8 EU member states have adopted rules guiding pharmacists’ conduct in e-pharmacies, providing detailed regulations aimed at safeguarding patients’ rights during the remote supply of medicines, health care products, and services. Considering these findings, the development of a common ethical framework for European pharmacists operating in e-pharmacies would be helpful for the development of ethics in their conduct on the internet. On the basis of the fundamental principles of biomedical ethics, we engaged in a reiterative process of reflection and discussion to develop an ethical framework tailored to the e-pharmacy context as our main contribution to knowledge. The proposed framework—representing a novel contribution to e-pharmacy ethics research—highlights ethical issues that should be incorporated into pharmacists’ codes of ethics or dedicated guidelines. These issues range from ensuring patient autonomy in selecting e-pharmacies to showing solidarity in the global e-pharmacy environment. Its novelty could be a major input for advancing e-pharmacy ethics. The following key messages are intended for pharmacists and their professional associations or other competent authorities interested in this field. Pharmacists’ codes of ethics should keep pace with the development of e-pharmacies to ensure they remain relevant and effective in guiding ethical conduct and decision-making in such an environment. Establishing a comprehensive, shared ethical framework for European pharmacists in e-pharmacies can foster a deeper understanding and appreciation of the opportunities afforded by emerging technologies. By facilitating the development of ethical conduct of pharmacists in e-pharmacies, such a framework can enhance patients’ well-being while promoting fundamental principles of autonomy, equity, and solidarity in this evolving field.